The “Sombrero-Shape” Super-Thin Pedicled ALT Flap for Complete Scrotal Reconstruction Following Fournier's Gangrene - Gianluca Sapino; Stephanie Gonvers; Mario Cherubino; Pietro G. di Summa (Archives of Plastic Surgery, 2022)
When the scrotal sac is entirely debrided following a Fournier gangrene, testes exposure poses unique challenges for the reconstructive surgeon. Despite the anterolateral thigh (ALT) flap is considered a workhorse in such context, aesthetic results are often suboptimal because of the lack of natural ptosis and patchwork appearance. We describe the use of a super-thin pedicled ALT flap for total scrotal reconstruction, modified according to a peculiar flap design and inset technique. A 42-year-old man was referred to our department for delayed total scrotal reconstruction 8 months after a Fournier gangrene extensive debridement. A super-thin pedicled ALT flap from the right thigh was designed: in the central portion of the ALT, a lateral skin paddle extension was marked to guarantee adequate posterior anchorage during insetting and ptosis of the scrotal sac. This particular flap arrangement has inspired the name “sombrero” as the shape is akin to the famous hat. No secondary refinements were needed, and the patient showed satisfying aesthetic and functional results at 12 months' follow-up. The ALT flap design “sombrero” modification proposed in this article can improve scrotum cosmesis and patient satisfaction in a single-stage single-flap procedure.